1999
DOI: 10.1074/jbc.274.38.27191
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Novel A Kinase Anchor Protein and a Myristoylated Alanine-rich C Kinase Substrate-like Analog from a Single Gene

Abstract: A unique Drosophila gene encodes two novel signaling proteins. Drosophila A kinase anchor protein 200 (DAKAP200) (753 amino acids) binds regulatory subunits of protein kinase AII (PKAII) isoforms in vitro and in intact cells. The acidic DAKAP200 polypeptide (pI ϳ3.8) contains an optimal N-terminal myristoylation site and a positively charged domain that resembles the multifunctional phosphorylation site domain of vertebrate myristoylated alanine-rich C kinase substrate proteins. The 15-kilobase pair DAKAP200 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…It is proposed that Ala is required for selective tethering of RI␣; Ser enables dual binding of RI␣ and RII␣ with similar affinities, and Ile, Val, or Leu promotes RII binding. The last suggestion is consistent with previously published alignments and conclusions indicating that Leu, Ile, and Val invariably occupy these positions in RII-binding proteins (9,23,24,37,52), and mutation of these residues to Ala compromises RII binding activity in all cases (19,37,52,59). Mutagenesis/expression studies on AKAP CE document Ser 244 or Val 244 (corresponding to position 6) are crucial determinants for R isoform selectivity.…”
supporting
confidence: 79%
“…It is proposed that Ala is required for selective tethering of RI␣; Ser enables dual binding of RI␣ and RII␣ with similar affinities, and Ile, Val, or Leu promotes RII binding. The last suggestion is consistent with previously published alignments and conclusions indicating that Leu, Ile, and Val invariably occupy these positions in RII-binding proteins (9,23,24,37,52), and mutation of these residues to Ala compromises RII binding activity in all cases (19,37,52,59). Mutagenesis/expression studies on AKAP CE document Ser 244 or Val 244 (corresponding to position 6) are crucial determinants for R isoform selectivity.…”
supporting
confidence: 79%
“…PSD modules (ϳ25-30 residues) of vertebrate myristoylated alanine rich C kinase substrate (MARCKS) proteins bind calcium-calmodulin, phospholipids, and actin; cooperate with N-terminal myristate to attach proteins to cell membranes; constitute specific target sites for protein kinase C (PKC)-catalyzed phosphorylation; and participate in dynamic regulation of the actin cytoskeleton that is associated with such fundamental cellular processes as motility and differentiation (7)(8)(9)(10)(11)(12). Thus, predicted properties of DAKAP200 suggest that this polypeptide is polyfunctional, differentially targeted to membranes, and involved in routing and integrating signals propagated by three important second messengers: cAMP, diacylglycerol, and calcium (6). Numerous caveats preclude acceptance of these ideas solely on the basis of information obtained from the amino acid sequence of DAKAP200.…”
Section: ؉mentioning
confidence: 99%
“…The discovery (6) of a novel cDNA and unique gene that encode Drosophila A kinase anchor protein 200 (DAKAP200) 1 provides an opportunity to investigate molecular mechanisms underlying integrated responses to multiple second messengers. DAKAP200 avidly binds regulatory subunits (RII) of protein kinase AII (PKAII) isoforms in vitro and in cells (6). The amino acid sequence of this 753-residue PKAII anchor protein also includes an Nterminal myristoylation motif and a potential "phosphorylation site domain" (PSD) (6).…”
Section: ؉mentioning
confidence: 99%
See 1 more Smart Citation
“…MESR2/AKAP200 encodes the Drosophila A kinase anchor protein, AKAP200, with a molecular mass of 200 kDa. AKAP200 binds the cyclic AMP-dependent protein kinase A (PKA) that has a non-uniform distribution in cells (Li et al, 1999). We previously demonstrated that overexpression of RacGAP(84C) perturbs the sub-cortical localisation of polymerised actin in embryonic cells (Guichard et al, 1997;Raymond et al, 2001), which would presumably prevent the normal localisation of AKAP200 with respect to the cytoskeleton.…”
Section: Racgap(84c) Mediates Crosstalk Between Gtpase Regulatory Promentioning
confidence: 99%